2010
DOI: 10.1007/s11115-010-0134-3
|View full text |Cite
|
Sign up to set email alerts
|

New Public Management: Promote the Public Sector Modernization Through Service Quality. Current Experiences and Future Challenges

Abstract: New Public Management, Service, Quality, SERVQUAL, IPA, Inland Revenue office, Greece,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 68 publications
2
9
0
Order By: Relevance
“…The main thrust of information drawn from the findings of this study is that the quality of the service provided to Greek Farmers by the MRDF is dependent on improving the human aspect of quality, and basically, skills that have to do with communication, their attitude and, in general, with the social skills of the employees and not so much with their knowledge level or the ministry's facilities. Lack of communication between consumers and service providers, has already been assigned to the "bureaucratic labyrinth" characteristic of the Greek public administration system (Kakouris and Meliou, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main thrust of information drawn from the findings of this study is that the quality of the service provided to Greek Farmers by the MRDF is dependent on improving the human aspect of quality, and basically, skills that have to do with communication, their attitude and, in general, with the social skills of the employees and not so much with their knowledge level or the ministry's facilities. Lack of communication between consumers and service providers, has already been assigned to the "bureaucratic labyrinth" characteristic of the Greek public administration system (Kakouris and Meliou, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The SERVQUAL instrument has been widely used to measure service quality in different countries, cultures and sectors such as: health sector (Kilbourne et al, 2004); retail trade (Naik et al, 2010); banking sector (Lam, 2002); hotels (Mey et al, 2006); sports (Kouthouris and Alexandris, 2005); telecommunications (van derWal et al, 2002); information systems (Carr, 2002); and for insurance companies (Gayathri et al, 2005). At the same time, there is a plethora of researches and studies examining the Greek public service quality in sectors such as the Citizen's Service Centers (Chatzoglou et al, 2013), the public hospitals (Karassavidou et al, 2009), the public social insurance system (Papanikolaou and Zygiaris, 2012), the public financial services (Kakouris and Meliou, 2011), the higher education (Zafiropoulos and Vrana, 2008) and even the Hellenic police (Boudouris et al, 2007). Nevertheless, there is no evidence in the literature on studies for the Greek MRDF or similar public services for farmers in Europe.…”
Section: Measuring Service Quality -Methodologymentioning
confidence: 99%
“…It was observed that mean value of macro variable "Improved Situation" is better in PSP. This is apparently due to better environmental conditions such as proper "Seating arrangements" (Cavana et al, 2007;Kakouris and Meliou, 2010), "Air conditioned and clean environment" (Yusoff et al, 2008;Islam et al, 2014), "Availability of drinking water" (DeitY, 2008;Chatzoglou et al, 2013) and "Provision of feedback" (Satapathy, 2014;Osman et al, 2014;Suri and Sushil, 2016). The mean value of "Capability Level of Actors" was also found better in PSP which may be due to better "Communication skills" (Parasuraman et al, 1988;Cavana et al, 2007) and "Service orientation" of employees (Bharwani and Jauhari, 2013;Al-Borie and Damanhouri 2013), better knowledge and punctuality of employees at service counters (Cavana et al, 2007;Kakouris and Meliou, 2010).…”
Section: Situation-actor-process Variablesmentioning
confidence: 99%
“…Nowadays, public administration is expected to keep improving its service (Holzer et al, 2009;Kakouris and Meliou, 2011). To meet this challenge, new management methods are being developed (Brinkerhoff and Wetterberg, 2013;Guenoun et al, 2016).…”
Section: Introductionmentioning
confidence: 99%